Liquid-liquid phase separation in atmospherically relevant particles consisting of organic species and inorganic salts - You, Yuan; Smith, Mackenzie L.; Song, Mijung; Martin, Scot T.; Bertram, Allan K. (International reviews in physical chemistry, 2014)
Laboratory studies of liquid-liquid phase separation in particles containing organic species and inorganic salts of atmospheric relevance are reviewed. The oxygen-to-carbon elemental ratio (O:C) of the organic component appears to be the most useful parameter for estimating, to a first approximation, the occurrence of liquid-liquid phase separation and the separation relative humidity (SRH) in these particles. A trend of decreasing SRH for increasing O:C was found for simple organic-inorganic mixtures (<11 species). Phase separation in particles composed of laboratory-produced secondary organic material and sulphate species and in ambient particles is generally consistent with this trend. A further constraint is that liquid-liquid phase separation was always observed for O:C < 0.5 and was never observed for O:C ≥ 0.8. For organic materials of intermediate O:C ranging from 0.5 to 0.8, phase separation in simple organic-inorganic mixtures was influenced by the organic functional groups represented. The organic-to-inorganic mass ratio (OIR) affected the occurrence of liquid-liquid phase separation in a small number of cases. A dependence on salt type was observed with 87% of the studied organics exhibiting the following trend in SRH values: (NH 4 ) 2 SO 4 ≥ NH 4 HSO 4 ≥ NaCl ≥ NH 4 NO 3 , consistent with previous salting-out studies and the Hofmeister series. Liquid-liquid phase separation does not appear to be strongly influenced by the number of species making up the organic material. The morphology of phase separated particles appears to depend on composition, including O:C of the organic material, the inorganic salt and the OIR.